Liquid retention agent, preparation method and lithium ion battery

By using ester-rich polymer I as a liquid retention agent in lithium-ion batteries, adsorbing the electrolyte and improving the ionic conductivity of the electrode sheet, the problem of capacity attenuation of lithium-ion batteries during high-speed charging is solved, and the capacity attenuation of lithium-ion batteries is achieved. Higher fast charging cycle capability.

CN119447301AActive Publication Date: 2025-02-14SVOLT ENERGY TECHNOLOGY CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411541794.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2025-02-14
Estimated Expiration
2044-10-31

AI Technical Summary

Technical Problem

Existing lithium-ion batteries are prone to cause capacity attenuation during high-speed charging, mainly due to insufficient liquid retention capacity of the electrode sheet, which cannot provide sufficient liquid medium to support the transmission of lithium ions.

Method used

Provide a liquid retention agent, including polymer I, whose structure is rich in ester groups, can effectively adsorb the electrolyte, reduce the loss of the electrolyte during the battery cycle, increase the ionic conductivity of the electrode sheet, and thus improve the fast charging of the battery. Circulation capability.

Benefits of technology

By using polymer I as the liquid retention agent, the fast charging and circulation capacity of the battery is significantly improved, the loss of the electrolyte is reduced, the ionic conductivity of the electrode sheet is improved, and the capacity attenuation problem is solved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention provides a liquid retention agent, a preparation method and a lithium ion battery. The liquid retention agent comprises a polymer I, the structural formula of the polymer I is shown in the formula I, R1 and R2 are independently selected from any one of H, C1-C3 alkyl and phenyl, and R1 and R2 are different; n is equal to 5-49. As the main effective component in the electrolyte of the battery is a small molecular ester compound, the polymer I serving as an oligomer rich in ester groups in a main chain has higher affinity to the small molecular ester compound in the electrolyte and can effectively adsorb the electrolyte on the main chain, and the electrolyte retention agent is used as an auxiliary material of an electrode material, so that the electrolyte retention effect is improved. The loss of electrolyte in the battery cycle process can be reduced, the ionic conductivity of the pole piece is improved, and the fast charge cycle capability of the battery is effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the technical field of battery materials, and specifically relates to a liquid retaining agent and a preparation method thereof, and a lithium ion battery. Background Art

[0002] With the rapid development of mobile technologies such as portable consumer electronics and electric vehicles, a new trend has emerged in the field of power batteries, namely focusing on high-rate fast charging technology. High-rate fast charging means that the battery can be charged at a faster speed, including 4C, 6C or even higher rates.

[0003] The key to achieving high-rate fast charging is to improve the charging capacity of the battery's negative electrode. The fast charging and discharging process depends on the embedding and de-embedding of lithium ions between the positive and negative electrodes. In order to achieve a better lithium ion transmission environment, the negative electrode needs to provide better conditions. However, if the electrode does not retain enough liquid, it will easily cause capacity attenuation. Insufficient liquid retention means that the electrode cannot provide enough liquid medium to support the transmission of lithium ions. This will cause problems in the battery during the charging and discharging process, such as reduced capacity or decreased performance.

[0004] How to increase the liquid retention of the electrode so that the battery's cycle performance can meet the usage scenario of high-rate fast charging is a technical problem that needs to be solved at present. Summary of the invention

[0005] The present application provides a liquid retaining agent and a preparation method thereof, and a lithium-ion battery, aiming to solve the problem that the existing lithium-ion battery pole pieces are prone to capacity decay during high-rate fast charging.

[0006] In order to solve the above problems, the first embodiment of the present application provides a liquid retaining agent, including a polymer I, wherein the structural formula of the polymer I is as shown in Formula I:

[0007]

[0008] Wherein, R1 and R2 are each independently selected from any one of H, C1-C3 alkyl and phenyl, and R1 and R2 are different;

[0009] n=5~49.

[0010] In some embodiments, R1 is selected from H and R2 is selected from phenyl.

[0011] In some embodiments, the molecular weight of the polymer I is 1,000 to 10,000.

[0012] In some embodiments, the solid content of the liquid retaining agent is 25% to 30%.

[0013] The second embodiment of the present application provides a method for preparing a liquid retaining agent, which is used to prepare the liquid retaining agent in any of the above embodiments, comprising the following steps:

[0014] Providing a first monomer and a second monomer, adding a dehydrating agent, stirring and mixing, and forming a mixture;

[0015] heating and pressurizing the mixture to allow the first monomer and the second monomer to undergo a polymerization reaction to generate a polymer I, thereby obtaining the liquid retaining agent;

[0016] Wherein, the structural formula of the first monomer is shown in Formula II:

[0017]

[0018] The structural formula of the second monomer is shown in Formula III:

[0019]

[0020] Wherein, R1 and R2 are each independently selected from any one of H, C1-C3 alkyl and phenyl, and R1 and R2 are different.

[0021] In some embodiments, the mass ratio of the first monomer, the second monomer, and the dehydrating agent is 1-2:1-1:0.05-0.1.

[0022] In some embodiments, the dehydrating agent comprises at least one of molecular sieves and anhydrous silica gel.

[0023] In some embodiments, the stirring and mixing temperature is 80-100°C.

[0024] In some embodiments, the polymerization reaction has a reaction temperature of 110-130° C. and a reaction pressure of 0-200 Pa.

[0025] In some embodiments, after the step of polymerizing the first monomer and the second monomer to generate the polymer I, the method further comprises:

[0026] Cooling the polymer I to room temperature, dissolving it in an organic solvent, and filtering out insoluble matter;

[0027] Wherein, the organic solvent includes N-methylpyrrolidone (NMP).

[0028] A third embodiment of the present application provides a lithium-ion battery, comprising a pole piece, wherein the pole piece comprises the liquid retaining agent in any of the above embodiments or comprises the liquid retaining agent prepared by the preparation method in any of the above embodiments.

[0029] The present application provides a liquid retaining agent, including polymer I, the structural formula of polymer I is shown in formula I, wherein R1 and R2 are independently selected from any one of H, C1-C3 alkyl and phenyl, and R1 and R2 are different; n=5-49. Since the main active ingredient in the electrolyte of the battery is a small molecule ester compound, polymer I, as an ester-rich oligomer in the main chain, has a higher affinity for the small molecule ester compounds in the electrolyte, and can effectively adsorb the electrolyte on the main chain. Using the liquid retaining agent as an auxiliary material for the electrode material can reduce the loss of the electrolyte during the battery cycle, improve the ionic conductivity of the electrode, and effectively improve the fast charging cycle capability of the battery. DETAILED DESCRIPTION

[0030] The technical solutions in the embodiments of the present application are described clearly and completely below. Obviously, the described embodiments are only a part of the embodiments of the present application, rather than all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present application.

[0031] In the description of the present application, it should be noted that, unless otherwise clearly specified and limited, the terms "connected" and "connected" should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection, an electrical connection, or can communicate with each other; it can be directly connected, or indirectly connected through an intermediate medium, or indirectly connected through a pipe or pipeline, and it can be the internal connection of two elements or the interaction relationship between two elements. For ordinary technicians in this field, the specific meanings of the above terms in this application can be understood according to the specific circumstances. In the description of the present application, the meaning of "multiple" is two or more, unless otherwise clearly and specifically defined. In addition, the terms "first" and "second" are used for descriptive purposes only, and cannot be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated. Therefore, the features defined as "first" and "second" can explicitly or implicitly include one or more features.

[0032] The first embodiment of the present application provides a liquid retaining agent, including a polymer I, the structural formula of the polymer I is shown in Formula I:

[0033]

[0034] Wherein, R1 and R2 are each independently selected from any one of H, C1-C3 alkyl and phenyl, and R1 and R2 are different;

[0035] n=5~49.

[0036] The main active ingredients in the battery electrolyte are small molecule ester compounds. Polymer I, as an ester-rich oligomer in the main chain, has a higher affinity for small molecule ester compounds in the electrolyte and can effectively adsorb the electrolyte on the main chain. Using this liquid retaining agent as an auxiliary material for electrode materials can reduce the loss of electrolyte during battery cycling, improve the ionic conductivity of the electrode, and effectively improve the fast charging cycle capacity of the battery. In addition, polymer I can be obtained by dehydration polymerization of two α-hydroxycarboxylic acids. The polymerization process does not require a catalyst or initiator, and the process is simple and easy to implement, which is conducive to large-scale promotion.

[0037] In some embodiments, R1 is selected from H and R2 is selected from phenyl.

[0038] The presence of phenyl side chains can provide additional adsorption sites for graphite and improve the dispersion level of polymer I. The main chain of the ester group can increase the interaction force with the ester small molecules, which is more conducive to the adsorption of electrolyte by polymer I. The alkyl side chains of appropriate length can ensure the stability of polyester while avoiding the large steric hindrance caused by the long alkyl chain, thereby preventing the diffusion rate and adsorption capacity of ester small molecules in polyester oligomers from being reduced.

[0039] In some embodiments, the molecular weight of polymer I is 1,000 to 10,000.

[0040] The molecular weight in this application refers to the weight average molecular weight of the polymer. It is understood that the molecular weight of polymer I can be any value of 1000, 2000, 3000, 4000, 5000, 6000, 7000, 8000, 9000, 10000 or a range between any two values. When the molecular weight of polymer I meets the above range, polymer I can have good strength and polarity.

[0041] In some embodiments, the solid content of the liquid retaining agent is 25% to 30%.

[0042] It is understandable that the solid content of the liquid retaining agent can be any value among 25%, 26%, 27%, 28%, 29%, 30%, or a range between any two values. When the solid content of the liquid retaining agent meets the above value range, it can ensure that the effective ingredients in the liquid retaining agent can cover all parts of the electrode, ensure the liquid retaining capacity of the electrode, and at the same time make the liquid retaining agent have a more ideal viscosity, so that it has a better bonding strength on the surface of the electrode.

[0043] The second embodiment of the present application provides a method for preparing a liquid retaining agent, which is used to prepare the liquid retaining agent in any of the above embodiments, comprising the following steps:

[0044] Providing a first monomer and a second monomer, adding a dehydrating agent, stirring and mixing, and forming a mixture;

[0045] heating and pressurizing the mixture to allow the first monomer and the second monomer to undergo a polymerization reaction to generate a polymer I, thereby obtaining a liquid retaining agent;

[0046] Wherein, the structural formula of the first monomer is shown in Formula II:

[0047]

[0048] The structural formula of the second monomer is shown in Formula III:

[0049]

[0050] Wherein, R1 and R2 are each independently selected from any one of H, C1-C3 alkyl and phenyl, and R1 and R2 are different.

[0051] The first monomer and the second monomer are two α-hydroxycarboxylic acids that can be dehydrated and condensed to form a polyester oligomer rich in ester groups in the main chain. They have a higher affinity for small molecule ester compounds in the electrolyte and can effectively adsorb the electrolyte on the main chain. During the polymerization process, no catalyst, initiator or end-capping is required, and the process is simple. Since the condensation reaction is reversible, the use of a dehydrating agent as an auxiliary agent can effectively remove the water content in the reaction system in time during the reaction, so that the reaction proceeds in the positive direction.

[0052] In some embodiments, R1 is selected from H, R2 is selected from phenyl, and the mass ratio of the first monomer, the second monomer and the dehydrating agent is 1-2:1-2:0.05-0.01.

[0053] When the mass ratio of the first monomer to the second monomer satisfies the above-mentioned range of values, it can ensure that the phenyl groups in the polymer I formed by the polycondensation have a reasonable percentage, which can provide additional adsorption sites for graphite and improve the dispersion level of the polymer I, while avoiding the large steric hindrance caused by too many side chains and avoiding the reduction of the diffusion rate and adsorption capacity of small ester molecules in the polyester oligomer.

[0054] In some embodiments, the dehydrating agent includes at least one of molecular sieves and dehydrated silica gel, wherein the molecular sieves include commercially available 3A molecular sieves and 4A molecular sieves; the dehydrating agent is further preferably 4A molecular sieves and dehydrated silica gel, mixed in a mass ratio of 1:1.

[0055] Molecular sieves have a highly ordered pore structure and can provide a large number of adsorption sites, so they have a high adsorption capacity, but they are sensitive to humidity. When the humidity is high, their adsorption capacity may decrease; dehydrated silica gel has a high hygroscopic capacity and can absorb moisture in the surrounding environment to keep it relatively dry, but compared to molecular sieves, dehydrated silica gel has a lower adsorption capacity and cannot handle high concentrations of humidity. Using a mixture of 4A molecular sieves and dehydrated silica gel as a dehydrating agent can make the dehydrating agent have a more ideal hygroscopic capacity throughout the reaction.

[0056] In some embodiments, the temperature of the stirring and mixing is 80-100°C.

[0057] It is understood that the stirring and mixing temperature (unit: ° C) can be any value among 80, 85, 90, 95, 100 or a range between any two values. When the stirring and mixing temperature meets the above range, it can ensure that the condensation reaction between the first monomer and the second monomer occurs.

[0058] In some embodiments, the polymerization reaction temperature is 110-130° C., and the reaction pressure is 0-200 Pa.

[0059] It can be understood that the reaction temperature of the polymerization reaction (unit: ° C) can be any value of 110, 115, 120, 125, 130 or a range between any two values, and the reaction pressure (unit: Pa) can be any value of 10, 20, 40, 60, 80, 120, 140, 160, 180, 200 or a range between any two values. The dehydration condensation reaction of polyester requires a large negative pressure to ensure that the dehydration speed is greater than the reaction speed. When the reaction temperature and reaction pressure of the polymerization reaction meet the above value ranges, it can ensure that the polymerization reaction proceeds in the positive direction.

[0060] In some embodiments, after the step of polymerizing the first monomer and the second monomer to generate the polymer I, the method further comprises:

[0061] Cooling polymer I to room temperature, dissolving it in an organic solvent, and filtering out insoluble matter;

[0062] Wherein, the organic solvent includes NMP.

[0063] By dissolving the polymer I in an organic solvent and filtering out the insoluble matter, the content of the effective component in the liquid retaining agent can be increased, and the liquid retaining capacity of the liquid retaining agent can be further improved.

[0064] A third embodiment of the present application provides a lithium-ion battery, including a pole piece, wherein the pole piece includes the liquid retaining agent in any of the above embodiments or includes the liquid retaining agent prepared by the preparation method in any of the above embodiments.

[0065] The following is a description of the liquid retaining agent, preparation method, and lithium ion battery provided by the present application in conjunction with specific embodiments:

[0066] Example 1

[0067] Example 1 provides a liquid retaining agent and a negative electrode plate, which are prepared by the following steps:

[0068] Provide glycolic acid and mandelic acid monomers, mix 5% by mass of 4A molecular sieve and 5% by mass of silica gel, stir with a screw stirring paddle at 80°C, dehydrate and condense at 120°C under a pressure of 100Pa to form a polymer I, recorded as PMGA, control the reaction time for 1h, cool to room temperature and then release the pressure, add NMP for ultrasonic dissolution for 30min, filter to remove insoluble matter, the product test solid content is 25, and a liquid retaining agent is obtained.

[0069] According to the positive electrode formula: 96.1% NCM811 + 2% carbon black + 0.7% carbon tube + 1% PVDF + 0.2% PMGA; the negative electrode formula: 96.4% graphite + 0.5% carbon black + 1.4% CMC + 1.5% SBR + 0.2% PMGA, the positive electrode sheet and the negative electrode sheet are prepared. The specific steps are as follows:

[0070] Add PVDF and NMP into a double planetary mixer, beat at medium speed, and disperse for 3 hours.

[0071] Add PVDF glue and SP into a double planetary agitator, disperse at medium speed for 1 hour, add NCM811 twice, add NMP, disperse at high speed for 2 hours each time, add 0.2% PMGA, disperse at medium speed for 30 minutes. After the end, add appropriate amount of NMP to adjust the slurry viscosity to a range suitable for coating.

[0072] The aluminum foil or carbon-coated aluminum foil is coated on one side or both sides by transfer coating or extrusion coating, and then baked in an oven at a temperature of 105° C. for 2 minutes to obtain a positive electrode sheet.

[0073] Add CMC and deionized water into a double planetary mixer and mix at medium speed for 1 hour.

[0074] CMC glue and 0.5% SP were added to a double planetary mixer and dispersed at medium speed for 2 hours. Then 4C graphite was added twice, and an appropriate amount of deionized water was added. The mixture was dispersed at high speed for 3 hours. SBR and PMGA were added and stirred at low speed for 0.5 hours. Then an appropriate amount of deionized water was added to adjust the slurry viscosity to a range suitable for coating.

[0075] The copper foil or carbon-coated copper foil is coated on one side or both sides by transfer coating or extrusion coating, and then baked in an oven at a temperature of 50-80° C. for 2 minutes to obtain a negative electrode sheet.

[0076] Embodiment 2:

[0077] The operation steps are the same as those in Example 1.

[0078] The positive electrode formula was modified to: 96.3% NCM811 + 2% carbon black + 0.7% carbon tube + 1% PVDF.

[0079] Embodiment 3:

[0080] The operation steps are the same as in Example 1.

[0081] The negative electrode formula was modified to: 96.6% graphite + 0.5% carbon black + 1.4% CMC + 1.5% SBR.

[0082] Comparative Example 1:

[0083] The operation steps are the same as in Example 1.

[0084] The positive and negative electrode formulas were modified as follows: positive electrode formula 96.1% NCM811 + 2% carbon black + 0.7% carbon tube + 1% PVDF + 0.2% polyacrylate liquid retaining agent; negative electrode formula 96.4% graphite + 0.5% carbon black + 1.4% CMC + 1.5% SBR + 0.2% polyacrylate liquid retaining agent.

[0085] Comparative Example 2:

[0086] The operation steps are the same as those in Example 1, except that 0.2% PMGA is eliminated from the positive and negative electrode formulas, and 0.2% of the main material is added.

[0087] The cycle performance of the embodiments and comparative examples was tested, and the results are shown in Table 1.

[0088] Table 1

[0089]

[0090] From Table 1 we can see:

[0091] In Example 1, in which a liquid retaining agent containing polymer I (PMGA) is added to both the positive and negative electrodes, the double charge and discharge retention rate and the cycle capacity under the 4C charging system are greatly improved compared with those of Example 2, and are also significantly better than those of Example 1, in which an equal amount of branched ester groups are added to the positive and negative electrodes as a polyacrylate liquid retaining agent.

[0092] Example 2 in which PMGA is added to the positive electrode improves the fast charging capability better than Example 3 in which PMGA is added to the negative electrode. However, regardless of adding PMGA only to the positive electrode or only to the negative electrode, the double charge and discharge retention rate and cycle capacity are better than those of Comparative Examples 1 and 2. This shows that the use of PMGA as a liquid retaining agent component improves the electrical properties of the electrode.

[0093] The above is a detailed introduction to a liquid retaining agent, a preparation method, and a lithium-ion battery provided in the embodiments of the present application. Specific examples are used in the present application to illustrate the principles and implementation methods of the present application. The description of the above embodiments is only used to help understand the technical solution and its core idea of ​​the present application; ordinary technicians in this field should understand that: they can still modify the technical solutions recorded in the aforementioned embodiments, or replace some of the technical features therein with equivalents; and these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present application.

Claims

1. A liquid retaining agent, characterized in that It includes a polymer I, the structural formula of the polymer I is shown in Formula I: Wherein, R1 and R2 are each independently selected from any one of H, C1-C3 alkyl and phenyl, and R1 and R2 are different; n=5~49。 2. A liquid retaining agent according to claim 1, characterized in that: R1 is selected from H, and R2 is selected from phenyl.

3. A liquid retaining agent according to claim 1, characterized in that: The molecular weight of the polymer I is 1,000 to 10,000.

4. A liquid retaining agent according to claim 1, characterized in that: The solid content of the liquid retaining agent is 25% to 30%.

5. A method for preparing the liquid retaining agent according to any one of claims 1 to 4, characterized in that: The steps include: Providing a first monomer and a second monomer, adding a dehydrating agent, stirring and mixing, and forming a mixture; heating and pressurizing the mixture to allow the first monomer and the second monomer to undergo a polymerization reaction to generate a polymer I, thereby obtaining the liquid retaining agent; Wherein, the structural formula of the first monomer is shown in Formula II: The structural formula of the second monomer is shown in Formula III: Wherein, R1 and R2 are each independently selected from any one of H, C1-C3 alkyl and phenyl, and R1 and R2 are different.

6. The method for preparing a liquid retaining agent according to claim 5, characterized in that: The mass ratio of the first monomer, the second monomer and the dehydrating agent is 1-2:1-2:0.05-0.

1.

7. The method for preparing a liquid retaining agent according to claim 5, characterized in that: The dehydrating agent includes at least one of molecular sieves and anhydrous silica gel.

8. The method for preparing a liquid retaining agent according to claim 5, characterized in that: The stirring and mixing temperature is 80-100°C; and / or, The reaction temperature of the polymerization reaction is 110-130° C., and the reaction pressure is 0-200 Pa.

9. The method for preparing a liquid retaining agent according to claim 5, characterized in that: After the step of polymerizing the first monomer and the second monomer to generate the polymer I, the method further comprises: Cooling the polymer I to room temperature, dissolving it in an organic solvent, and filtering out insoluble matter; Wherein, the organic solvent includes N-methylpyrrolidone.

10. A lithium ion battery, comprising a pole piece, characterized in that: The electrode comprises the liquid retaining agent as described in any one of claims 1 to 4 or comprises the liquid retaining agent prepared by the preparation method as described in claims 5 to 9.

Citation Information

Patent Citations

  • Liquid retention additive, electrode slurry, preparation method of electrode slurry, electrode plate and lithium ion battery

    CN116525939A

  • Production of polyhydroxycarboxylic acid

    JP1995173265A

  • Method for producing polymer

    JP2023136318A

  • Dispersing agent for cathode slurry of lithium ion battery and preparation method and application therefor

    US20230299297A1

  • Organic acid catalyst for polylactic acid synthesis

    WO2007145195A1